2020
DOI: 10.1080/09513590.2020.1816722
|View full text |Cite
|
Sign up to set email alerts
|

The potentialities of oxytocin receptor inhibitors for endometriosis therapy

Abstract: Objective: Genital endometriosis (GE) is a widespread gynecological disease which requires its further pathogenesis investigation and search for new effective treatments. The known data of oxytocin receptor presence in endometrioid heterotopy smooth muscle cells give some grounds to assume oxytocin participation in the pathogenesis of endometriosis. The present study objective was to evaluate oxytocin level in peripheral blood (PB) in patients with endometriosis associated pain syndrome and to estimate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Guo et al 38 for dysmenorrhea), and lower testosterone (which increases pain sensitivity) (reviewed in Dinsdale et al 6 ), both of which could contribute to higher RMET scores. Indeed, Yarmolinskaya et al 5 reported that compared to unaffected women, women with endometriosis had higher serum oxytocin, and that serum oxytocin levels positively predicted pelvic pain intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guo et al 38 for dysmenorrhea), and lower testosterone (which increases pain sensitivity) (reviewed in Dinsdale et al 6 ), both of which could contribute to higher RMET scores. Indeed, Yarmolinskaya et al 5 reported that compared to unaffected women, women with endometriosis had higher serum oxytocin, and that serum oxytocin levels positively predicted pelvic pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis and polycystic ovary syndrome (PCOS), the two most common female reproductive disorders, involve atypical hormonal profiles that contribute to diverse problematic symptoms for affected women. [1][2][3][4][5][6][7][8][9][10] Endometriosis involves the proliferation and inflammation of endometrial or endometrial-like tissue beyond the uterine boundary, 1 with pelvic pain, and risk for the disorder, linked to high levels of estrogen and oxytocin and low testosterone. [2][3][4][5][6] By contrast, PCOS involves irregular or absent ovulation, hirsutism, and polyfollicular ovaries, most of which involve elevated testosterone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, excessive OT secretion is associated with preterm labor, prenatal eclampsia, and postpartum hemorrhage [173]. In patients with endometriosis-associated pain syndrome, OT level in peripheral blood is significantly higher; administration of OTR inhibitors can cause authentic decrease of endometrioid heterotopy area as shown in an animal model of surgically induced endometriosis [181]. Excessive OT secretion may delay ovulation and interrupt implantation while embryo transfer can be facilitated by application of OT antagonist atosiban as shown in a patient with cervical stenosis [182] and by a single oral dose of nolasiban in women undergoing in vitro fertilization [183].…”
Section: Discussionmentioning
confidence: 99%